Households’ Earthquake Disaster Preparedness Behavior: The Role of Trust in and Help From Stakeholders - Ao, Yibin; Tan, Liyao; Tan, Ling; Zhong, Jinglin; Zhang, Hongying; Wang, Yan; Wang, Tong (Frontiers in Environmental Science, 2022)
Earthquake is one of the most serious natural disasters. Taking scientific and reasonable earthquake preparedness measures can effectively reduce casualties and economic losses caused by earthquakes. It is important to understand how residents choose such earthquake preparedness measures to guide them accordingly. However, the current research has failed to address rural areas in developing countries and has inconsistency conclusions for two aspects related to stakeholders involved: the assistance the victims can get from stakeholders for applying earthquake preparedness measures and the trust in stakeholders’ disaster relief abilities. In this study, the rural residents affected by Wenchuan earthquake, Ya 'an earthquake and Yibin earthquake were taken as the research objects, and 674 valid questionnaires were obtained through field household surveys. A Multinominal Logit Model (MNL) was constructed to explore the influence of villagers' trust in the disaster relief ability of stakeholders and the help they can get from stakeholders on their preparedness behavior. The results show that the less trust the villagers have on the government and the community, and the more help they can get from the outside while preparing measures, the more inclined they are to take the disaster preparedness measures. Furthermore, the education level of villagers in earthquake-stricken areas has significant positive impacts on people’s earthquake preparedness behavior. People who are not born in rural areas are more likely to take earthquake preparedness measures. In addition, male, young and married villagers are more likely to take earthquake preparedness measures in their daily lives. This study enriches the theory of rural disaster prevention and mitigation, and provides reference for the practice of disaster prevention and mitigation in earthquake-stricken rural areas.